Osteoradionecrosis of the hyoid presenting as acute airway compromise. Issue 9 (5th July 2021) - Wang, Sherrie; Stanisce, Luke; Begun, Zoe; Wilson, Traeden; Ahmad, Nadir; Kubicek, Gregory J.; Koshkareva, Yekaterina
Abstract: Background: Osteoradionecrosis (ORN) of the mandible is a well‐known complication of radiation therapy for head and neck cancer. However, few reports have described hyoid bone ORN and its clinical implications. Methods: We describe a retrospective case series of previously irradiated patients who were seen with sudden airway compromise, found to have underlying pathological hyoid fractures secondary to osteoradionecrosis. Results: Six patients within postchemoradiation period (3–9 months) for oropharyngeal squamous cell carcinoma were seen with acute‐onset dyspnea. Computed topography (CT) imaging was remarkable for severe airway luminal narrowing and pathological hyoid fractures. All six patients required urgent intervention with direct laryngoscopy and tracheostomy. Intraoperatively, five patients were seen with exposed necrotic hyoid bones. Conclusion: The hyoid and its associated musculature strongly influence upper airway patency. ORN may compromise its physiological function and leads to acute airway compromise. Hyoid ORN may hold significant and imperative clinical implications in head and neck cancer post‐treatment surveillance.